Determinants of customers' intention to use Islamic personal financing: the case of Malaysian Islamic banks - Amin, Hanudin; Abdul Rahman, Abdul Rahim; Laison Sondoh, Stephen; Ang, Magdelene Choi Hwa (Emerald Group Publishing Limited, 2011)
Purpose – Islamic banking and finance is an emerging global industry founded on Islamic ethical precepts. Just as in the case of conventional banks, Islamic banks are expected to offer products that consider the needs of their customers. The present study investigates the effects of the following factors: attitude; social influence; religious obligation; government support; and pricing, on the intention to use Islamic personal financing. Design/methodology/approach – The sample comprised of 150 customers of two fully fledged Islamic banks in Malaysia: Bank Islam Malaysia Berhad and Bank Muamalat Malaysia Berhad. Data were obtained through a face-to-face survey using semi-structured questionnaire. Out of a total of 150 responses, only 136 responses were usable for further analysis. The study used factor analysis, correlation and regression to analyse the data. Findings – The study found three determinants to be significant in influencing the intention to use Islamic personal financing, namely, attitude, social influence and pricing of Islamic personal financing. Religious obligation and government support were found to be insignificant predictors. Research limitations/implications – The first limitation of the study is the narrow focus of the survey on the customers of two fully fledged Islamic banks. The second limitation of this work concerns the measurement employed to gauge bank customers’ acceptance of Islamic personal financing. Despite these limitations, the findings of this study provide invaluable insights into factors affecting the bank customers’ intention to use Islamic personal financing, especially in the case of Malaysian Islamic banks. Originality/value – This empirical study on the determinants of Islamic financing using the survey method contributes towards a better understanding of the customers’ expectations for Islamic financial products. Managers of Islamic banks can now comprehend better the factors that influence bank customers’ decision in patronizing Islamic personal financing. Hence, more effective strategies can be recommended to attract bank customers to use Islamic personal financing. Not to mention, the findings of this study should be of value to Islamic banks in terms of expanding their customer base.